Implementation of Information-Based Time Management Counseling Services to Improve the Learning Effectiveness of Class XI Students at MAN 6 Aceh Besar - Mukhlis; Isra Miranda; Fakhri Yacob (Journal of Education, Pedagogy and Teacher Training, 2025)
Learning effectiveness is an aspect of knowledge, attitude, competence, and skills that have been achieved by students according to the predetermined target. Information-based Time Management Counseling Services as one of the encouragements to equip students with the introduction and understanding of the time management process which greatly influences their learning effectiveness. The purpose of this study was to analyze the increase in student learning effectiveness after studying with the Counseling Service. This study used an experimental method with One Group Pretest-Posttest Design. The data collection technique with a Likert scale was distributing questionnaires to students. The number of students analyzed in the study was 15 students of class XI MAN 6 Aceh Besar. The data analysis technique used the Normality Test and T-Test and N-Gain Test. The results showed that there was an increase in student learning effectiveness. The results of the T-Test test were 22.336 with a significance of 0.000 which means 0.00 <0.05 The average N-Gain value of Learning Effectiveness was 0.57 in the Moderate category. It can be concluded that the information-based time management counseling service approach can improve the learning effectiveness of MAN 6 Aceh Besar students